Urban Plants for Medicinal Purposes - Nur Dina Shazani, Binti Mohd Azam (Universiti Malaysia Sarawak (UNIMAS), 2009)
Phytochemical screenings were conducted on ten selected urban plants commonly planted in the city of Kuching and Unimas campus of Kota Samarahan. The plant species selected were Allamanda cathartica, Syzygium campanulatum, Callistemon vimina/is, Plumeria alba, Tecoma stans, Mussaenda philippica, Mesua ferrea, Hibiscus rosa sinensis, Filicium decipiens and Hibiscus tiliaceus. Young and mature leaves were analyzed and their chemical contents were compared. Only few plant species showed positive results for both alkaloids and saponins analyses tests. A. cathartica, T. stans, and M. ferrea were found to have large amount of alkaloids while S. campanulatum and T. stans contain large amount of saponins. F. decipiens, T. stans and C. viminalis showed large amount of components on developed TLC plate. Two selected plant species which were F. decipiens and T. stans were also analyzed using NMR and FTIR. Various functional groups were detected through the analyses such as aldehyde, ketones and hydroxyl groups.